Science laboratory dynamics and acquisition of science process skill among form four science female students - Algaretnam, Sarojini Devi (2003)
Laboratory activities have been regarded as an integral and essential aspect of learning experience in school science teaching. So to achieve the goals of the science curriculum, there was a need to enhance the diagnostic study of the science laboratory environment. Thus, the general purpose of this study was to investigate the nature of the laboratory dynamics and determine the dominant types of variables existing in a science laboratory. The study also sought to investigate the relationships between variables such as lesson structures, class setting, student interactions and student behaviours in a science laboratory. Besides that, the researcher attempted to examine the relationship between the above variables and student acquisition of science process skills. Hence, a conceptual framework based on an adapted causal model p roposed by Pizzini and Sherpardson (1992) was used In the study.